Effect of scabby wheat in starter pig diets - D S Pollmann; B A Koch (Kansas Agricultural Experiment Station Research Reports, 1982)
Two studies using a total of 64 starter pigs (averaging 16-18 lbs initial weight) to evaluate the influence of varying levels of vornitoxin-contaminated wheat on performance was conducted. In both trials it appears that when vomitoxin levels exceed 1 ppm, a reduction in performance was evident. Feed refusal was evident particularly the first week on the vomitoxin-contaminated wheat. No symptoms of sickness, nor an influence on tissue size and function, were observed. The pigs were unable to compensate for depression in gains after withdrawal of vomitoxin-contaminated wheat.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Scabby wheat; Starte pig diets